Help! I'm a prisoner in the library - Clifford, Eth, 1915-; Hughes, George, 1943- (Boston : Houghton Mifflin, 1979)
Two girls spend an adventurous night trapped inside the public library during a terrible blizzard.
G4
Keywords: Libraries -- Fiction; Blizzards -- Fiction